Teacher-Student Translanguaging Interaction: A Discourse Analysis of Eliciting Responses in EFL Classrooms - Fadly Umadji; Hasanuddin Fatsah; Muziatun; Rasuna Talib; Rahman Taufiqrianto Dako (Universitas Islam Negeri Palopo, 2026)
This study investigates the strategic utilization of translanguaging within teacher-student interactional sequences to elicit and facilitate student responses in the English as a Foreign Language (EFL) classroom of SMA Negeri 11 Gorontalo Utara. Set within the rural, multi-ethnic educational context of Gentuma Village, which is deeply characterized by the local sociocultural philosophy of Huyula (mutual cooperation), this research challenges traditional monolingual biases in language pedagogy. Employing a qualitative descriptive case study design oriented towards classroom discourse analysis. The analysis strictly integrates Doff’s (2012) taxonomy of elicitation techniques encompassing questioning, visual aids, games, texts, and non-verbal cues, with contemporary translanguaging pedagogical frameworks. The results demonstrate that the teacher systematically orchestrates a sophisticated